Application of Yager’s Fuzzy Logic in Sociological Research: An Instance of Potential Payoff - Uddin, Mohammed Faruque (European Scientific Journal, ESJ, 2017)
This article exemplifies Yager’s theory of fuzzy logic for interpersonal communication to the area of social research. Taking the dilemma between qualitative and quantitative approaches into the account, there is an anticipation to make a merge between these two. There is an enormous prospect to turn up scientists’ philanthropic innovations if they could use fuzzy logic in social science researches! However, by using fuzzy logic in sociological research there is a great deal of opportunity to study the social facts related to poverty, consumption, employment, intersubjectivity, social capital, environment, gender etc. How can we use Yager’s theory of Fuzzy Logic to analyze the relationship between social capital and labor market partcicpation? From the experiential connection in Bangladesh society, I try to seek this answer using a hypothetical quantification of attributes.